Changing Patterns of Great Lakes Vessel Ownership As a Factor in the Economic Development of Toronto, 1850-1860 - Davidson, Malcolm (Urban History Review / Revue d'histoire urbaine, 1988)
The changing patterns in the numbers and kinds of Great Lakes vessels owned by Toronto businessmen and mariners across the decade from 1850 to 1860 are analyzed within the context of the larger urban economy. A comparison of the data collected for 1850 and 1860 indicates that Toronto entrepreneurs through the 1850s reduced their financial commitments to steam-powered vessels and expanded their commitment to sail. It is suggested that this preference was a financially sensible one and may have been a concomitant of the heavy investments required to develop a northern and western hinterland. The relationship of these findings to studies on Toronto businessmen by White, McCalla, and Baskerville is indicated.